Platelet aggregation measured by single-platelet counting and using PFA-100 devices. (3rd October 2018) - Dovlatova, Natalia; Heptinstall, Stan
Abstract: Platelets play a crucial role in haemostasis and thrombosis and evaluation of platelet function in vitro, in particular platelet aggregation responses, has been one of the most common and useful ways of evaluating the risk of bleeding and thrombotic events and assessing the effects of various compounds and conditions on platelets. Traditional approaches to assessing platelet aggregation require specialised equipment and trained laboratory personnel and have other limitations. Studying platelet aggregation in whole blood offers a more physiologically relevant measurement. Additionally, certain approaches could be more widely available than in specialised laboratories. Here we summarise the application of the platelet function analyser (PFA-100), an accessible first point-of-care test for platelet function in whole blood, and the less established, but promising approach of assessing platelet aggregation by single-platelet counting that can also be performed in whole blood. The possibilities of a wider and more accessible application of the latter methodology are also discussed.